2014
DOI: 10.1103/physrevb.89.205419
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects on the magneto-optical response of magnetoplasmonic dimers

Abstract: The effect that dipole-dipole interactions have on the magneto-optical (MO) properties of magnetoplasmonic dimers is theoretically studied. The specific plasmonic versus magnetoplasmonic nature of the dimer's metallic components and their specific location within the dimer play a crucial role in the determination of these properties. We find that it is possible to generate an induced MO activity in a purely plasmonic component, even larger than that of the MO one, therefore dominating the overall MO spectral d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
(48 reference statements)
1
27
0
Order By: Relevance
“…The amplitude and phase relations of the four dipoles determine the optical and magneto-optical response of the Ni/SiO 2 /Au dimer in the far field [31,35,36]. In transmission geometry, the excitation of two orthogonal electric dipoles near the plasmon resonance condition causes the polarization of linearly polarized incident light to rotate and become elliptical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude and phase relations of the four dipoles determine the optical and magneto-optical response of the Ni/SiO 2 /Au dimer in the far field [31,35,36]. In transmission geometry, the excitation of two orthogonal electric dipoles near the plasmon resonance condition causes the polarization of linearly polarized incident light to rotate and become elliptical.…”
Section: Resultsmentioning
confidence: 99%
“…In all these realizations, the magnetic constituent is in direct contact with the noble metal. Dimer nanodisks wherein a dielectric layer separates the ferromagnet and noble metal [31,35,36] and composite arrays of pure ferromagnetic and noble metal nanoparticles [24] have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…This way, and in addition to the well-known case of plasmonic nanodisks exhibiting electric dipole resonances, in recent years it has also been demonstrated that nanoholes in optically thin metallic films exhibit "hole plasmon resonances" that resemble those of equivalent nanodisks. 24,25 This effect is so strong that has even allowed measuring the MO activity in pure noble metal resonant nanoelements. 16,17,18 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 Apart from the obvious interest of investigating inverted systems exhibiting optical magnetism in the visible range, an open question is the feasibility of actually realizing an active control of this optical magnetism and the corresponding light-matter interaction.…”
mentioning
confidence: 99%
“…Similarly to the results reported in refs. [129,130], also in this configuration the magnetic field-induced SLRs in the nickel nano-disks promote an enhancement of those in the gold ones, thus demonstrating that this approach may lead to new possibilities for the realization of tunable hybrid magneto-plasmonic crystals. A similar approach was also proposed previously by Caminale et al [146], who investigated the magnetooptical response of chemically synthesized iron oxide magnetic nanocrystals, optically coupled with ordered planar arrays of plasmonic meta-atoms, where they were able to arbitrary superimpose or detune the LSPRs of the nanoparticles arrays with respect to the dominant magneto-optical resonances of the magnetic meta-atoms to either merge or separate the purely plasmonic and the magnetic contributions in the magneto-optical spectrum to tune the enhancement of the magneto-optical signal.…”
Section: Far-field Diffractive Coupling In Magneto-plasmonic Crystalsmentioning
confidence: 64%